How to draw all the animals for kids - Koch, Alli (Bend, OR : Paige Tate & Co., 2021)
Learn to draw one's favorite animals in 5 minutes or less! From forest friends like a fox, bear, and bunny rabbit, to jungle critters like a sloth, toucan, and tiger, Alli Koch will show how to draw the readers favorite creatures using step-by-step instructions in this modern drawing book for kids!
Jungle -- Safari -- Sea -- Down under -- Farm -- Forest -- Arctic -- Pets -- Insects.
3-6
4.6
Keywords: Animals in art -- Juvenile literature; Drawing -- Technique -- Juvenile literature; Animals in art; Drawing -- Technique; Illustrated works; Handbooks and manuals